Exploring factors influencing dietary intake during hospitalization: Results from analyzing nutritionDay's database (2006–2013). (August 2020) - Kontogianni, Meropi D.; Poulia, Kalliopi Anna; Bersimis, Fragkiskos; Sulz, Isabella; Schindler, Karin; Hiesmayr, Michael; Chourdakis, Michail
Summary: Background & aims: Hospital food consumption can affect patients' outcome leading to prolonged hospital stay or even increased mortality. In the present study, the nutritionDay database was analyzed (period 2006–2013) to explore the reasons for reduced food intake and associated factors during hospitalization as reported by the patients per se. Methods: Data from 113, 930 adult patients (male 49.9%; mean age 64.0 ± 18.1 y, mean BMI 25.7 ± 6.0 kg/m 2 ) (from 4519 units, 1358 hospitals, 54 countries) were included. Dietary intake and reasons for reduced food intake were reported and analyzed. Results: Only 41.6% of patients reported to have consumed all their served meal, whereas 9.3% ate nothing although allowed to eat. Variables like presence of caner, having nausea/vomiting, feeling tired, not feeling hungry and not liking food's taste increased the likelihood of consuming "¼ of the meal" but not "nothing". Variables like having gastrointestinal disorder, being bedrest, receiving nutritional support and not liking food's smell increased the likelihood of both decreased (¼ compared to ½) and null (nothing compared to ¼) food consumption (all p < 0.001). Conclusions: Food consumption during hospitalization is associated with variables related to both patients' condition (e.g. clinical, physical) and factors related to the quality of hospital food.